The political papacy: John Paul II, Benedict XVI, and their influence - Gillis, Chester (Paradigm Publishers, 2006)
John Paul II and Benedict XVI -- The battle with totalitarian regimes -- On the world stage -- Relations with Jews -- Relations with Muslims -- Social and moral issues